2007
DOI: 10.1152/ajpgi.00361.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of the thrombin/protease-activated receptor 1 pathway in intestinal ischemia-reperfusion injury in rats

Abstract: CXC chemokines, including human interleukin-8 and rat cytokine-induced neutrophil chemoattractant-1, play a crucial role in the pathogenesis of intestinal inflammation induced by ischemia-reperfusion (I-R). Thrombin and its specific receptor, protease-activated receptor 1 (PAR1), act as important players in inflammation. However, the association between thrombin activation and chemokine production during I-R has not been well studied. We investigated whether thrombin and PAR1 might be involved in the pathophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…25 Herein, in vivo, we observed a decrease of TAT formation at 60 min post-reperfusion when the kidney was preserved with anticoagulants. Since a direct link between thrombin activity and pro-inflammatory response has been established in IR context, in mice 26 and rat, 27 our results further suggest that EP217609-dependent "thrombin" inhibition may limit inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…25 Herein, in vivo, we observed a decrease of TAT formation at 60 min post-reperfusion when the kidney was preserved with anticoagulants. Since a direct link between thrombin activity and pro-inflammatory response has been established in IR context, in mice 26 and rat, 27 our results further suggest that EP217609-dependent "thrombin" inhibition may limit inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have implied that tissue hypoxia affects the integrity of adherens junctions and promotes increased vascular permeability. This breakdown of the barrier has been shown to be associated with increased levels of inflammatory mediators such as thrombin, histamine, and VEGF (27), which further contribute to adverse outcomes of vascular dysfunction. Vascular permeability has thus become a hallmark of numerous autoimmune and inflammatory conditions including I/R (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…it was previously reported that cinc-1 levels increased during small intestinal i/r injury and that cinc-1 was related to the extent of mucosal damage with neutrophil accumulation (21,22,35). in addition, a previous study demonstrated that pre-treatment with an anti-cinc-1 monoclonal antibody attenuated reperfusion injury in the small intestine, in association with a reduction in TnF-α and MPo levels, thereby prolonging survival (36).…”
Section: A B Bmentioning
confidence: 92%